Self-reported occupational accidents and affecting factors among the adult population/ Acidentes de trabalho autorreferidos e fatores que afetam a população adulta - Özdemir Mi̇kai̇l; Saveb, Dilsad (Cadernos Brasileiros de Terapia Ocupacional, 2021)
Introduction: As official occupational accident records are insufficient in developing countries such as Turkey, self-reported numbers are a better reflection of the real scope of occupational accidents among Turkish workers. Objective: This study aims to determine the factors affecting occupational accidents in Turkey. Method: This cross-sectional study re-evaluated data from a total of 42,360 participants, were obtained from the ‘Occupational Accidents and Occupational Health Problems’ module of the Household Labor Force Survey conducted by TurkStat. Results: The prevalence of occupational accidents in the prior 12 months was 2.1%. The probability of an occupational accident for men was 1.78 times higher than for women (95% CI: 1.38-2.30). Workers who had not completed primary education [OR=1.91 (95% CI: 1.09-3.3)] and those who were divorced [OR=2.26 (95% CI: 1.40-3.63)] were more likely to have an accident at work, when compared to university graduates and unmarried employees, respectively. Conclusion: Male gender, low educational level, and divorced marital status can be considered risk factors and require more attention and a control program to prevent the loss of labor due to occupational accidents in Turkey. This is the first, most comprehensive, and up-to-date study using extensive national data to examine the factors that affect occupational accidents in Turkey.